Capture methods of Caiman latirostris Daudin, 1802 (Crocodylia, Alligatoridae) in northern Uruguay, with notes of defensive and feeding behaviours - Claudio Borteiro; Francisco Gutiérrez; Marcelo Tedros; Francisco Kolenc; Luciano Martins Verdade (Revista de Biologia Neotropical, 2023)
Caiman latirostris is a Neotropical crocodilian for which there is scarce natural history information in regard to other species, as also about survey methods used by field researchers. In this work we report the capture methodology implemented during population monitoring in northern Uruguay and some observations about defensive and feeding behaviours. We found the use of a metallic clamp as very useful for capturing juveniles and subadult individuals (< 120 cm total length) in vegetated habitats, while a wire snare was used for adults. Regardless locomotor escape, we provide a reappraisal of defensive behaviours in the presence of humans, with particular comments on tonic immobility. In addition, we suggest an apparent case of carcass consumption (scavenging) for the species, a presumedly common behaviour but sometimes hard to observe in wild crocodilians.